Evaluasi Penerapan PSAK 72 dan Implikasinya terhadap Likuiditas, Solvabilitas, dan Profitabilitas PDAM Surya Sembada Surabaya - Noer Khofifah Apriliana; Ravika Mutiara Savitra (Politeknik Ganesha Medan, 2026)
The development of accounting standards requires companies to present transparent and reliable financial reports, especially in revenue recognition. The implementation of Statement of Financial Accounting Standards (PSAK) 72 regarding revenue from contracts with customers has the potential to cause changes in the financial performance of companies, including Regionally Owned Enterprises (BUMD) such as the Regional Drinking Water Company (PDAM). This study aims to analyze the impact of the implementation of PSAK 72 on the financial performance of PDAM Surya Sembada Surabaya as measured by liquidity, solvency, and profitability ratios. The research method used is a comparative quantitative approach using secondary data in the form of PDAM Surya Sembada Surabaya's financial statements for the period 2019–2020. The analytical tools used include financial ratio analysis and comparative tests before and after the implementation of PSAK 72. The results of the study indicate that the implementation of PSAK 72 causes changes in the pattern of revenue recognition that impacts liquidity and profitability ratios, while the solvency ratio tends to be relatively stable. These changes reflect the adjustment of accounting policies in financial reporting after the implementation of the new standard. The implications of this research show that the implementation of PSAK 72 can improve the quality of PDAM financial reports by presenting more relevant, transparent and accountable information, and can be used as evaluation material for management and local governments in making financial decisions.